A high‐confidence Physcomitrium patens plasmodesmata proteome by iterative scoring and validation reveals diversification of cell wall proteins during evolution. Issue 2 (17th February 2023) - Gombos, Sven; Miras, Manuel; Howe, Vicky; Xi, Lin; Pottier, Mathieu; Kazemein Jasemi, Neda S.; Schladt, Moritz; Ejike, J. Obinna; Neumann, Ulla; Hänsch, Sebastian; Kuttig, Franziska; Zhang, Zhaoxia; et al.
Summary: Plasmodesmata (PD) facilitate movement of molecules between plant cells. Regulation of this movement is still not understood. Plasmodesmata are hard to study, being deeply embedded within cell walls and incorporating several membrane types. Thus, structure and protein composition of PD remain enigmatic. Previous studies of PD protein composition identified protein lists with few validations, making functional conclusions difficult. We developed a PD scoring approach in iteration with large‐scale systematic localization, defining a high‐confidence PD proteome of Physcomitrium patens (HC300). HC300, together with bona fide PD proteins from literature, were placed in Pddb . About 65% of proteins in HC300 were not previously PD‐localized. Callose‐degrading glycolyl hydrolase family 17 (GHL17) is an abundant protein family with representatives across evolutionary scale. Among GHL17s, we exclusively found members of one phylogenetic clade with PD localization and orthologs occur only in species with developed PD. Phylogenetic comparison was expanded to xyloglucan endotransglucosylases/hydrolases and Exordium‐like proteins, which also diversified into PD‐localized and non‐PD‐localized members on distinct phylogenetic clades. Our high‐confidence PD proteome HC300 provides insights into diversification of large protein families. Iterative and systematic large‐scale localization across plant species strengthens the reliability of HC300 as basis for exploring structure, function, and evolution of this important organelle.